The Periodontal Tissue Health Status of Patients with Chronic Kidney Disease - Ani Subekti; Agustin Wulan Suci Dharmayanti; Miranda Gita Wahyuningtyas; Agnes Lia Renata (Borneo Scientific Publishing, 2026)
Chronic Kidney Disease (CKD) is a significant global health issue, affecting approximately 700 million people worldwide. This study investigates the periodontal health of CKD patients in Banyumanik District, Semarang, Central Java, Indonesia, where the prevalence of CKD is notably high. A cross-sectional analysis involving 44 CKD patients from three community health centers was conducted. Data were collected through medical records and periodontal examinations using the Community Periodontal Index of Treatment Needs (CPITN) and the Gingival Index (GI). Results indicated that 70% of participants exhibited moderate to severe gingival inflammation, with an average GI score of 1.75. The majority required phase I periodontal treatment, including scaling and root planning. Significant correlations were found between gingival inflammation and factors such as hemodialysis history and the duration of CKD. Patients undergoing hemodialysis showed higher levels of gingival inflammation compared to those who were not. The findings highlight the critical need for regular periodontal assessments and interventions in CKD patients to mitigate oral health complications and improve overall quality of life. This study underscores the importance of integrating oral health management into the care of CKD patients, particularly in regions with high prevalence rates.